Global Aesthetics, Local Realities: Internationalization Discourse in Higher Education Digital Media - Ade Wijaya, Duitarama; Oktaviani, Fitri Hariana; Prasetyo, Bambang Dwi (Alphabet, 2025)
This study analyzes how language and symbols in digital media are used to represent the discourse of internationalization in Indonesian higher education, focusing on the official Instagram account of an institution disguised as FI. Using a descriptive-qualitative approach with critical thematic analysis (Lawless & Chen, 2019), this study explores 16 Instagram posts selected based on visibility and level of audience interaction. The results of the analysis show that FIs construct an institutional image as a global entity through the use of the English language, visual symbols such as foreign flags, overseas university logos, and imagery of prestigious academic locations. However, local identity only appears as an additional element in the form of dances, traditional clothing, or traditional cuisine displayed decoratively to support international events. The findings reveal the tension between responding to the demands of internationalization and commitment to local values, and reflect the orientalist logic of cultural representation. This study contributes to the understanding of institutional identity construction through digital media, as well as providing a critical reading of power relations in the discourse of globalization of higher education.